Diagnostic analysis on service quality parameters: a comparison of select banks in Uttarakhand, India. (2015) - Singh, Saurabh; Kamal, Raj; Kumar, Devendra
The process of economic liberalisation initiated in India in 1991 paved the way for the entry of private sector banks and foreign banks, which fundamentally changed the structure of the Indian banking industry. Consequently the banking sector today faces an intense competitive environment which is forcing them to adapt to new ways and innovate in their attempt to survive. Financial services, particularly banks, often compete in the market with nearly similar kinds of service. In such a scenario the primary competitive weapon available to them is differentiating themselves based on their quality of service offered by them. The present study applies SERVQUAL instrument to diagnose the service quality of two selected banks for their comparative evaluation. The study revealed that individually both the banks still have a long journey ahead on all the five dimensions of SERVQUAL instrument.